A corpus study of structural types of lexical bundles in MUET reading texts - Christina Ong, Sook Beng; Yuen, Chee Keong (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
In view of the recurrent issues concerning university students’ inability to comprehend reading passages in their studies, texts used in a Malaysian examination for tertiary education were analysed. This study investigates the use of lexical bundles (LBs) in the reading passages of Malaysian University English Test (MUET). A specialised corpus of MUET test papers comprised of only the reading passages grouped into two main disciplines namely arts and science was built. Besides identifying commonly used LBs, this study aims to compare and contrast structural types of LBs found in arts and science-based texts. Using WordSmith Tools version 5, the lists of LBs of the identified disciplines were generated. They were analysed qualitatively based on Biber, Conrad & Cortes’ (2004) Structural Taxonomy. Findings revealed that the number of LBs in both disciplines differs significantly but many similar LBs are employed. It was also evident that science-based texts tend to employ more NP-based and VP-based LBs while the most commonly used structure in arts-based texts is dependent clause. In general, PP-based LBs are very significant in both science and arts-based texts. The extent to which LBs are specific to particular disciplines is therefore confirmed and an overview of how LBs in texts construct information is also obtained. Pedagogically, teachers should consider incorporating corpora-based material, to exploit consciousness raising tasks and not to emphasise too much on grammatical items so that LBs do not go unnoticed.